Unraveling the Impact of Combined NaF/RbF Postdeposition Treatments on the Deeply Buried Cu(In,Ga)Se2/Mo Thin‐Film Solar Cell Interface - Bombsch, Jakob; Avancini, Enrico; Carron, Romain; Handick, Evelyn; Garcia-Diez, Raul; Hartmann, Claudia; Félix, Roberto; Abou-Ras, Daniel; Ueda, Shigenori; Wilks, Regan G.; Bär, Marcus (Advanced Energy and Sustainability Research, 2021)
Cu(In,Ga)Se2 (CIGSe) is a promising absorber material for thin‐film photovoltaic devices. A key procedure to achieve high efficiencies is the application of alkali fluoride postdeposition treatments (PDT) of the CIGSe surface. While the effects of the PDT on the directly impacted CIGSe front surface have been subject to extensive studies, less is known about the impact on the deeply buried CIGSe/Mo interface. Exposing the CIGSe absorber backside by stripping it off the Mo back contact allows to use surface‐sensitive photoelectron spectroscopy to study the chemical and electronic structure of this interface in unprecedented detail. CIGSe /Mo stacks prepared using NaF only and combined NaF/RbF (with optimal and excess amount of RbF) PDT are studied. Rb is detected accumulating at the backside of the RbF‐treated CIGSe absorbers in conjunction with a depletion of Na. The exposed CIGSe backsides display a Cu‐deficient surface region, with increased presence of Rb correlating with a decreased Cu content. Rb appears to be incorporated into the Cu‐deficient absorber region as previously detected on the front surface. However, in contrast to the front surface, no distinct, secondary RbInSe‐type phase is found at the back surface. The impact of performance‐enhancing NaF/RbF postdeposition treatments on the deeply buried Cu(In,Ga)Se2/Mo thin‐film solar cell interface is studied by making it accessibly by stripping off the absorber from the back contact. Despite Rb accumulating at this back interface and pronounced Cu deficiency of the Cu(In,Ga)Se2 back surface, in contrast to the Cu(In,Ga)Se2 front surface no RbInSe‐type compound is formed.